Association between Spirituality and Oral Health-related Behavior among Adult Population in Chengalpattu District - A Cross-sectional Analysis - Muthuselvan Anupreya; Ravi Karthikayan; Subramaniyan Vishnuprasad (Wolters Kluwer Medknow Publications, 2024)
Purpose: Integrating existing theory and research, this paper is a study about the association between spirituality and oral health-related behavior among the Chengalpattu adult population. Materials and Methods: Based on Hodge's framework, we claimed that spirituality has an indirect association with oral health practices. The adult population was made to answer a questionnaire consisting of several questions supporting their spiritual orientation and also their oral health behavior. Results: Participants who are spiritually oriented persons reported moderate-to-good oral health-related behavior. Conclusion: This study result indicates the importance of spiritual health in accomplishing healthy behavior.